Aplikasi Informasi Posko Bencana Alam Berbasis Android - Setiawati, Irma Yunita; Handojo, Andreas; Purbowo, Anita Nathania (Jurnal Infra, 2015)
Within the last 10 years, there have been so many natural disasters such as tsunami, earthquakes, and the eruption of Mount Merapi in Yogyakarta. Many emergency shelters were built to accommodate the disasters survivors. It caused problems in processing information regarding existing aid. An application named "Post Natural Disaster Information" was created to make it easier to process the information.This is an useful application for both the donors and the posts. This app has a feature to provide information on available data from each post, so that donors know the needs of certain posts. It takes advantage of Android devices to provide information about the posts to the users. It could be posts logistics or data shelters refugees in post. In addition to the person in charge of the post, this application helps organizing the logistics command post as logistical transfer. This application could send a broadcast to the users who have been already logged in. It also provides information in the form of a website. This application was made by Eclipse IDE in the Java programming language for Android and using the PHP programming language for websites with CodeIgniter framework.The test results show that the application is running well on some devices such as Android 4.2 (Jelly Bean), Android 4.4 (Kitkat). Applications can run the update feature post, broadcast, maintain logistics data and find posts locations well.